Industry Perspective on Journalism Education Curriculum in Malaysia - Norhafezah Yusof; Awan Ismail; Rizalawati Ismail; Norizah Aripin; Azahar Kassim; Mohd Sobhi Ishak (Malaysian Journal of Learning and Instruction, 2018)
Purpose -This study investigated media and communication practitionersâ€™ perspectives on the journalism education curriculum in Malaysia. Curriculum plays an important role in providing quality education for students. Journalism is a dynamic field that integrates industrial experience and fundamental knowledge in the field from higher educational institutions. Scholars in the field are divided on the issue of whether it is important for academia to consider input from industrial players in shaping the curriculum on journalism education in higher institutions of learning.